2016
DOI: 10.20944/preprints201611.0143.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Experimental Study of Mortars with Recycled Ceramic Aggregates. Deduction and Prediction of the Stress-Strain

Abstract: The difficult current environmental situation, caused by construction industry residues containing ceramic materials could be improved by using these materials as recycled aggregates in mortars, with their processing causing a reduction in their use in landfill, contributing to recycling and also minimizing the consumption of virgin materials. Although some research is currently being carried out into recycled mortars, little is known about their stress-strain (σ-ε); therefore this work will provide the experi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
(80 reference statements)
1
6
0
Order By: Relevance
“…The water absorption capacity of all the recycled aggregates proved to be greater than that of the natural aggregate (Table 1), a fact which has also been reported by other researchers [13,[17][18][19]22,26,[42][43][44]. With respect to recycled aggregates, those obtained from crushing the fine and coarse fraction of CDW1 achieved the highest and lowest absorption capacity, respectively.…”
Section: Fine Aggregates Propertiessupporting
confidence: 81%
See 1 more Smart Citation
“…The water absorption capacity of all the recycled aggregates proved to be greater than that of the natural aggregate (Table 1), a fact which has also been reported by other researchers [13,[17][18][19]22,26,[42][43][44]. With respect to recycled aggregates, those obtained from crushing the fine and coarse fraction of CDW1 achieved the highest and lowest absorption capacity, respectively.…”
Section: Fine Aggregates Propertiessupporting
confidence: 81%
“…Most of the mortar mixes manufactured with higher percentages of recycled aggregate presented lower mechanical properties than those of conventional mortar [13,14,16,17,19,20]. However, certain authors have established that there were minor influences on the properties of mortar mixes produced with a replacement ratio of up to 20% [21,22], 25% [19] or 40% [15] of recycled aggregate in substitution of natural aggregate. According to several researches [23][24][25][26] the improvements on the mortars'…”
Section: Introductionmentioning
confidence: 99%
“…In Table 4 the results corresponding to the physical and mechanical properties of the CRM and UM studied, respectively, are shown. These results (open porosity and absorption [ 29 ]; density , fm , E and drying shrinkage [ 34 ]) were analyzed in previous works. The objective of the current work is to establish their relationship with porosity.…”
Section: Resultsmentioning
confidence: 99%
“…The standards used were the Spanish UNE (UNE-EN 1015-10 [ 32 ], UNE-EN 1936 [ 33 ], and ASTM standards, respectively. More details of the tests for these properties can be found in previous publications by the authors [ 29 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies on polycarbosilanederived SiC ceramic 25 and SiC/SiC composite 26,27 have shown that porosity decreases and mechanical properties improve with the increasing number of PIP cycles. Zhu et al 28 show that increasing pyrolysis temperature and the concentration of SiC fillers in polycarbosilane polymer result in improved mechanical properties in two-dimensional Carbon/ SiC (C/SiC) composites fabricated using the PIP process.…”
Section: Introductionmentioning
confidence: 99%